A taxonomic revision of the genus Cephalotaxus (Taxaceae) - Lang, Xue-Dong; Su, Jian-Rong; Lu, Shu-Gang; Zhang, Zhi-Jun (Phytotaxa, 2013)
A taxonomic revision of the genus Cephalotaxus is presented based on taxonomic literature, herbarium specimens and field work. We conclude the genus to contain seven species: C. oliveri, C. fortunei, C. griffithii, C. alpina, C. harringtonii, C. nana and C. hainanensis. We accept C. hainanensis and C. griffithii as separate species and not as synonyms of C. mannii, because type specimens of these taxa are not identical in the shape and size of the leaves. A key to all species, distribution maps and photographs of Cephalotaxus are also provided.